Manajemen Keuangan Lembaga Pendidikan Al Qur’an Muhammadiyah (Studi Kasus pada LPQ Darul Muttaqin Nglegok) - Bambang Wahrudin; Wawan Kusnawan (xxxx-xxxx, 2022)
Financial management in Qur'an educational institutions is still not optimal because the management of the institution has not implemented good management in the process of its activities. This attracts the author to conduct qualitative-descriptive research by taking the object of one of the Qur'anic educational institutions that has developed with the number of students as many as 90 children. Through participant observation in the process of LPQ Darul Muttaqin Nglegok's activities, in-depth interviews with the head of the institution, ustadz-ustadz and guardians of students and documentation used as a method of extracting data, as well as using substantive descriptive data analysis. This study shows a finding that applicatively the financial management process has been applied in the Darul Muttaqin Nglegok Qur'an educational institution substantively covering the process of planning for the procurement of funds through work meetings at the beginning of the year, and the preparation of program and activity plans. The process of utilization through the implementation of programs and activities as well as accountability includes activities through weekly monitoring and evaluation, student guardian meetings as a substantive form of management implementation.